Policy-making in eu security and defense an institutional perspective - Dijkstra, Hylke; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
EU foreign policy has long been considered the exclusive domain of member states. This book challenges such state-centered wisdom by analyzing the influence of Brussels-based EU officials in the area of security and defence. Using case studies and unique insights from over a hundred interviews this book shows how everyday policy is made in practice.
Keywords: Science; Science; Science, general